Meningkatkan Daya Saing UMKM Pangan Melalui Pelatihan 5R Pada Industri Kecil Di Wilayah Kecamatan Tengaran - Maya Utami Dewi; Aris Sarwo Nugroho; Migunani; Sumaryanto; Yuli fitrianto; Nanik Qosidah; Ayyub Hamdanu Budi Nurmana; Sri Yulianingsih; Luthfy Purnanta Anzie; Siswanto; Dhevi Dadi Kusumaningtyas (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
MSMEs have a strategic role in the Indonesian economy, especially in creating jobs and improving people's welfare. However, many MSMEs face challenges in operational efficiency and workplace management. The 5R concept (Ringkas, Rapi, Resik, Rawat, and Rajin) is a method that has been proven to increase productivity and work efficiency. This community service activity was carried out by the Lecturer Team of the University of Computer Science and Technology who held a 5R Training for 20 MSME actors in Sugihan Village, Tengaran District, Semarang Regency. This training aims to improve understanding and application of the 5R principles in the work environment, so that MSMEs can operate more efficiently and increase competitiveness. The methods used include theory sessions, discussions, and questions and answers. The results of the training activities, participants were able to absorb 80% of the material provided related to the implementation of 5R, related to increasing awareness of the importance of workplace organization, production efficiency, and cleanliness and safety of the business environment. It is hoped that in the future, participants through this training can provide real benefits in increasing productivity and the quality of their products.